2009
DOI: 10.1021/ie900322x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Model-Based Control of an Experimental Reverse-Osmosis Water Desalination System

Abstract: This work focuses on the design and implementation of a nonlinear model-based control system on an experimental reverse-osmosis (RO) membrane water desalination system to address large set-point changes and variations in feedwater salinity. A dynamic nonlinear lumped-parameter model is derived using firstprinciples, and its parameters are computed from experimental data to minimize the error between model predictions and experimental RO system response. This model then is used as the basis for the design of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 21 publications
(42 reference statements)
0
38
0
Order By: Relevance
“…Data for model development were generated using the UCLA spiral-wound Mini-Mobile-Modular (M3) pilot RO desalination system shown schematically in Figure 1. 3,35,36 The M3 system was designed for permeate water production capacity up to 1.2 m 3 /h (7560 gallons/day) for brackish water (5000 mg/L TDS) operating at 75% recovery and up to 0.64 m 3 /h (4058 gallons/day) for seawater desalination (at recovery of 40%), using up to 18 spiralwound elements in various configurations. In the present study, a configuration of 6 elements (one per pressure vessel) in series was utilized with the system operating in a total recycle mode 35 that adjusted both an electrically actuated needle valve (valve V-1) (model VA8 V-7-0-10, ETI Systems, Carlsbad, CA) on the retentate stream of the M3 RO system and the pump VFD.…”
Section: Methodsmentioning
confidence: 99%
“…Data for model development were generated using the UCLA spiral-wound Mini-Mobile-Modular (M3) pilot RO desalination system shown schematically in Figure 1. 3,35,36 The M3 system was designed for permeate water production capacity up to 1.2 m 3 /h (7560 gallons/day) for brackish water (5000 mg/L TDS) operating at 75% recovery and up to 0.64 m 3 /h (4058 gallons/day) for seawater desalination (at recovery of 40%), using up to 18 spiralwound elements in various configurations. In the present study, a configuration of 6 elements (one per pressure vessel) in series was utilized with the system operating in a total recycle mode 35 that adjusted both an electrically actuated needle valve (valve V-1) (model VA8 V-7-0-10, ETI Systems, Carlsbad, CA) on the retentate stream of the M3 RO system and the pump VFD.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, there are several research works [29][30][31] interested in reverse osmosis. In this paper, our objective is determining the bond graph model of the reverse osmosis component by component in order to facilitate the detection and location of faults.…”
Section: General Description Of the Systemmentioning
confidence: 99%
“…Current literatures suggested that the transition from one steady state to another steady state for RO process changes in different applications. Bartman et al altered the flow rate less than ~1 min within a wide range of operation in UCLA experimental RO membrane water desalination system [33]. Sassi et al reported that pseudo steady-state model of RO can be considered for time-step more than 0.25 h [34].…”
Section: Evaluation and Comparison Of Mppt Controllersmentioning
confidence: 99%